Flavonoid derivative 7,8-DHF attenuates TBI pathology via TrkB activation - Agrawal, Rahul (Biochim Biophys Acta, 2015)
Traumatic brain injury (TBI) is followed by a state of metabolic dysfunction, affecting the ability of neurons to use energy and support brain plasticity; there is no effective therapy to counteract the TBI pathology. Brain-derived neurotrophic factor (BDNF) has an exceptional capacity to support metabolism and plasticity, which highly contrasts with its poor pharmacological profile. We evaluated the action of a flavonoid derivative 7,8-dihydroxyflavone (7,8-DHF), a BDNF receptor (TrkB) agonist with the pharmacological profile congruent for potential human therapies. Treatment with 7,8-DHF (5 mg/kg, ip, daily for 7 days) was effective to ameliorate the effects of TBI on plasticity markers (CREB phosphorylation, GAP-43 and syntaxin-3 levels) and memory function in Barnes maze test. Treatment with 7,8-DHF restored the decrease in protein and phenotypic expression of TrkB phosphorylation after TBI. In turn, intrahippocampal injections of K252a, a TrkB antagonist, counteracted the 7,8-DHF induced TrkB signaling activation and memory improvement in TBI, suggesting the pivotal role of TrkB signaling in cognitive performance after brain injury. A potential action of 7,8-DHF on cell energy homeostasis was corroborated by the normalization in levels of PGC-1α, TFAM, COII, AMPK and SIRT1 in animals subjected to TBI. Results suggest a potential mechanism by which 7,8-DHF counteracts TBI pathology via activation of the TrkB receptor and engaging the interplay between cell energy management and synaptic plasticity. Since metabolic dysfunction is an important risk factor for the development of neurological and psychiatric disorders, these results set a precedent for the therapeutic use of 7,8-DHF in a larger context.